2008
DOI: 10.1073/pnas.0805354105
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Hsp90 activates osteoclast c-Src signaling and promotes growth of prostate carcinoma cells in bone

Abstract: Hsp90 inhibitors are being evaluated extensively in patients with advanced cancers. However, the impact of Hsp90 inhibition on signaling pathways in normal tissues and the effect that this may have on the antitumor activity of these molecularly targeted drugs have not been rigorously examined. Breast and prostate carcinomas are among those cancers that respond to Hsp90 inhibitors in animal xenograft models and in early studies in patients. Because these cancers frequently metastasize to bone, it is important t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
74
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 47 publications
7
74
0
Order By: Relevance
“…1A), and, consistent with previous findings (20,21), 17-AAG also increased RANKLstimulated osteoclast formation in a dose-dependent manner (Fig. 1, B and C).…”
Section: Hsp90 Inhibitors Enhance Osteoclast Formation In Associationsupporting
confidence: 81%
See 1 more Smart Citation
“…1A), and, consistent with previous findings (20,21), 17-AAG also increased RANKLstimulated osteoclast formation in a dose-dependent manner (Fig. 1, B and C).…”
Section: Hsp90 Inhibitors Enhance Osteoclast Formation In Associationsupporting
confidence: 81%
“…In addition to 17-AAG, we have demonstrated that other structurally unrelated HSP90 inhibitors also enhance osteoclast formation (20,22). To date, the mechanism by which HSP90 inhibitors stimulate osteoclast formation has not been clearly defined, although Src kinase and the elevated expression of the essential osteoclast transcription factor microphthalmia-associated transcription factor (MITF) may play roles (21,22). However, HSP90 inhibition itself seems unlikely to be directly critical in 17-AAG actions on osteoclasts because many of the RANKL signaling pathways required for osteoclast formation (e.g.…”
mentioning
confidence: 99%
“…Additionally, 17-N-Allylamino-17-demethoxygeldanamycin (17-AAG); retaspimycin hydrochloride (IPI-504), two Hsp90 inhibitors, provided no benefit to CRPC patients (55,56). The poor therapeutic effect of Hsp90 inhibitors may be the consequence of inhibiting widespread client proteins and may thereby result in activation of oncogenic signaling pathways such as Src and co-chaperone Hsp27 up-regulation (57,58). Inhibition of Cdc37, a co-chaperone of Hsp90 that is overexpressed in cancer cells, may represent a better drug target in cancers (59).…”
Section: Discussionmentioning
confidence: 99%
“…Cytoplasmic c-Src is a well-studied HSP90 client protein and its interaction with HSP90 is required for Src maturation (47). However, we have shown previously that pharmacological disruption of HSP90 association with mature c-Src induces a transient but distinct increase in c-Src activity (48,49). Release of enzymatically competent c-Src from HSP90 relieves its auto-inhibition and permits phosphorylation of Tyr-416 in the activation loop.…”
Section: Discussionmentioning
confidence: 99%